Sustainability of dairy sheep farming: Examples from Greece and Spain - Tzouramani I.; Zelovitis J.; Intxaurrandieta J.M.; Eguinoa P. (Innovation for sustainability in sheep and goats, 2019)
In the European Union (EU), the European Commission has included in its Europe 2020 strategy the ‘Sustainable growth: promoting a more resource efficient, greener and more competitive economy.’ The EU has also recognized the positive role of agriculture and livestock in rural areas in delivering ‘multiple economic, social, environmental and territorial benefits.’ In the framework of the research project FLINT (‘Farm Level Indicators for New Topics in Policy Evaluation’), one of the main aims was to provide a review of indicators and to collect the related data from farms to determine the level of sustainability. The concept of sustainability refers not only to the triple-bottom-line approach – Profit (economic), Planet (environmental) and People (social) - but also to other issues like innovation, risk management, market outlets and quality labeling, advisory services, and climate change. The small ruminant sector was one of those that included this, as its contribution to the strategy of sustainable growth has recognized. In this paper, we present two cases referring to the dairy sheep sector in Greece (Ipeirus) and Spain (Navarra). A collection of core indicators will be presented to describe the sustainability level for dairy sheep farming between the two countries. Due to the small sample size, dairy sheep farming in both countries shows a high degree of heterogeneity and diversity. Only qualitative factors, like the use of processing at the farm level, the use of short supply chains and qualitative labels could be derived to support the sustainable view of traditional producing systems. The assessment of the sector’s sustainability level helps to develop the appropriate decisions/policies either at the local farm or larger territorial level.
2. Joint Seminar of the Subnetworks on Nutrition and on Production Systems of the FAO-CIHEAM Network for Research and Development in Sheep and Goats, 2017/10/03-05, Vitoria-Gasteiz (Spain)